Does Ultrasonically Measured Subcutaneous Abdominal Fat Relate with Grades of Non-Alcoholic Fatty Disease of Liver (NAFDL)? (Medical Forum Monthly, 2022)
Objective: This study was designed to assess the relationship of SAFT and the presence of NAFDL along with its severity grade in T2DM and Obesity.Study Design: Observational / cross section studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Rai Medical College Sargodha from January to December, 2021.Materials and Methods: This study was carried out on the patients presenting in medical OPD, from 40 to 70 years of age, both genders. Obesity was assessed by the simplest and most practiced parameter of obesity as “Looking Obese” or having a “sacking or protuberant tummy”. T2DM was confirmed on the basis of available blood sugar and HbA1c record. After applying inclusion (obesity and T2DM) and exclusion criteria, volunteering participants were asked to get an abdominal ultrasound (USG) examination for grading of Hepatic Parenchymal Echogenicity (HPE) in NAFDL and to measure Subcutaneous Abdominal Fat Thickness (SAFT) through the same acoustic window. Subcutaneous Abdominal Fat Thickness (SAFT) measured in mm during USG examination was divided into 4 grades, G1 (0 – 25), G2 (25.01 – 50), G3 (50.01 – 75) and G4 (75.01 – 100) for the convenience of evaluation.Results: 420 females and 186 males were included in this study. Among the 420 females, 270 had G1 HPE, out of these 13% had G1 SAFT, 82% had G2 SAFT, 4% had G3 SAFT and none had G4 SAFT. There were 150 females exhibiting G2 HPE, out of these 92% had G1 SAFT, 4% had G2 SAFT, 4% had G3 SAFT and none had G4 SAFT. No female had G3 HPE. Out of 186 males, 102 males had G1 HPE, out of these 47% had G1 SAFT, 53% had G2 SAFT and none had G3 or G4 SAFT. There were 84 males exhibiting G2 HPE, out of these 29% had G1 SAFT, 71% had G2 SAFT and none had G3 or G4 HPE.Conclusion: The relationship between upper quadrant and lower quadrant can be the subject of some future studies. The organizations can invite opinion for the recommendation of standard points of window.